2001
DOI: 10.1002/mds.1139
|View full text |Cite
|
Sign up to set email alerts
|

Rate of progression in Parkinson's disease: A 6‐[18F]fluoro‐L‐dopa PET study

Abstract: The aim of this study was to investigate the rate of progression in Parkinson's disease (PD) with 6-[(18)F]fluoro-L-dopa (FDOPA) positron emission tomography (PET). We investigated 21 patients with PD and eight healthy controls. Ten of the patients were de novo at the time of the first PET scan and antiparkinsonian medication was started thereafter, with a favourable response. A FDOPA PET scan was carried out twice at an approximately 5-year interval. The regions of interest were drawn on individual magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
153
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 34 publications
13
153
2
1
Order By: Relevance
“…7 Previous studies have shown a linear reduction of striatal DaT binding in early PD, with estimated annual rates of decline ranging from 4% to 10%. [8][9][10][11][12] In our study, assuming a constant decline, the estimated absolute annual rate of decline of striatal DaT binding was around 5%. It is important to highlight that we could not calculate the relative rate of decline compared to age-expected normal values at the time of the first scan, since we did not have those data.…”
Section: Discussionmentioning
confidence: 46%
“…7 Previous studies have shown a linear reduction of striatal DaT binding in early PD, with estimated annual rates of decline ranging from 4% to 10%. [8][9][10][11][12] In our study, assuming a constant decline, the estimated absolute annual rate of decline of striatal DaT binding was around 5%. It is important to highlight that we could not calculate the relative rate of decline compared to age-expected normal values at the time of the first scan, since we did not have those data.…”
Section: Discussionmentioning
confidence: 46%
“…In advanced stages, dopaminergic degeneration becomes slower, and although the gradient is maintained, the degree of asymmetry diminishes (Hilker, Schweitzer, et al, 2005;Hilker, Thomas, et al, 2005;Nandhagopal et al, 2009). The mean annual decline in [ 18 F]dopa uptake ranges from 8% to 12% in the putamen and from 4% to 6% in the caudate and it is considerably more than the decline typical of aging (Nurmi et al, 2001;Pavese, Rivero-Bosch, Lewis, Whone, & Brooks, 2011). Moreover, presynaptic dopaminergic PET imaging has been used to estimate the duration of preclinical PD and it has shown 30%-55% loss of putamen dopaminergic function at the time of symptom onset (de la Fuente-Fernández et al, 2011;Hilker, Schweitzer, et al, 2005;Hilker, Thomas, et al, 2005;Lee, 2000).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…[47][48][49] In early PD patients treated with L-dopa putamen, 18 F-dopa uptake has been reported to decline annually by around 10% of baseline (5% of the normal mean), whereas caudate uptake falls at a slower rate. Similar rates of loss of putamen dopamine transporter binding have been reported with 18 F-CFT PET 50 and with 123 I-␤-CIT, 51 123 I-FP-CIT, 52 and 123 I-IPT SPECT.…”
Section: Monitoring Pd Progressionmentioning
confidence: 99%